2003
DOI: 10.2174/1566524033479618
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-Induced Inflammatory Liver Injuries

Abstract: IL-18 is a pleiotropic cytokine and is produced by various types of cells including activated macrophages, particularly Kupffer cells. IL-18 has potential to activate inflammatory responses through induction of IFN-gamma production in collaboration with IL-12. Somewhat paradoxically, IL-18 also has the capacity to induce allergic responses via induction of IL-4 production by T helper cells and to activate mast cells and basophils to release atopic effector molecules such as histamine. Indeed, IL-18 is involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 0 publications
0
53
0
1
Order By: Relevance
“…It is possible that MyD88 signaling in the regenerating liver depends on IL-1 and IL-18 rather than LPS. However, a number of experiments in hepatocyte cultures suggest that IL-1␤ inhibits hepatocyte replication (41,42), while IL-18 expression has been associated with liver injury rather than cell proliferation (43,44). IL-18 is also known as IFN-␥-inducing factor, and recently we and others have demonstrated that IFN-␥ inhibits hepatocyte proliferation and liver regeneration (45,46).…”
Section: Discussionmentioning
confidence: 98%
“…It is possible that MyD88 signaling in the regenerating liver depends on IL-1 and IL-18 rather than LPS. However, a number of experiments in hepatocyte cultures suggest that IL-1␤ inhibits hepatocyte replication (41,42), while IL-18 expression has been associated with liver injury rather than cell proliferation (43,44). IL-18 is also known as IFN-␥-inducing factor, and recently we and others have demonstrated that IFN-␥ inhibits hepatocyte proliferation and liver regeneration (45,46).…”
Section: Discussionmentioning
confidence: 98%
“…These procytokines are cleaved by caspase-1 activated by the NLRP3 inflammasome. In turn, mature IL-1b and IL-18 upregulate innate immune responses in local immune cells (23,33). Specifically, Kupffer cells (the resident macrophages of the liver) can propagate the hepatic innate inflammatory response through the production of proinflammatory TNF-␣ (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Lck is an attractive target to block T cell activation for a number of reasons (Tsutsui et al, 2003). First, Lck is crucial in the activation of T cells causing clonal expansion and generation of a cytotoxic T cell response (Weiss and Littman, 1994).…”
Section: Discussionmentioning
confidence: 99%